Challenges and Constraints in the Economic Development of Rural Areas in Afghanistan and Solutions for Development - Fayaz Gul Mazloum Yar; Ahmad Sabir Noori (CV. Syntax Corporation Indonesia, 2024)
This study aims to investigate the challenges and constraints of economic development in Afghanistan's rural areas and to propose solutions to overcome these obstacles. Rural economic development in Afghanistan faces significant challenges due to infrastructure deficiencies, financial and social limitations, and high rates of labor migration to urban areas. In this regard, the study seeks to analyze these inhibiting factors and provide practical, policy-oriented solutions to improve the economic conditions of Afghanistan’s rural communities. This research utilizes a mixed-methods approach, combining qualitative and quantitative methods. Data were collected through semi-structured interviews and quantitative surveys from various groups, including farmers, small business owners, and local officials in several rural regions of Afghanistan. The data were analyzed through content analysis and statistical methods. Findings indicate that the primary challenges to economic development in these areas include a lack of infrastructure, insufficient financial facilities, and limited access to technical and vocational training. Additionally, the results suggest that support for small businesses, infrastructure development, and vocational training could significantly improve rural economic conditions. This research not only offers policy recommendations for government institutions and development organizations but also adds to the theoretical literature on rural economic development in Afghanistan, potentially serving as a guide for effective, localized policymaking.